Endovascular Management of Post Traumatic Lower Extremity Pseudoaneurysm: An Evidence Based Case Report - Darwis, Patrianef; Subrata, Feyona H (UI Scholars Hub, 2020)
Introduction. Increasing incidence of trauma all over the world will increase the risk of vascular trauma, so will the prevalence of pseudoaneurysm. Post traumatic pseudoaneurysm occurs within days or months and commonly diagnosed as hematoma in its early presentation. An effective, less invasive, and low-cost treatment with high rate of survival is needed by patients with post traumatic pseudoaneurysm. Endovascular surgery is one of the less invasive techniques. This case report was made to find out the effectivity of endovascular surgery in the treatment of post traumatic pseudoaneurysm. Method. Literature searching was performed in Cochrane Library, EBSCOhost, ClinicalKey, Pubmed, dan Proquest database. Five articles were found to be relevant to the topic. There were only case report articles with level of evidence level 4 based on Oxford Centre for Evidence Based Medicine 2011. Results. Endovascular surgery approach was effective in the treatment of post traumatic lower extremity pseudoaneurysm for those who were not eligible for open surgery or conservative technique. Patients were given long term dual antiplatelet therapy for 6-12 months. Within 6-18 months of follow up, the pseudoaneurysm was completely obliterated and the patients were symptoms free. Conclusion. Based on level of evidence number 4 endovascular surgery approach can be used for post traumatic pseudoaneurysm patients who were not eligible for open surgery or conservative technique. Further research is needed to know the side effect and complication of endovascular surgery